The Influence of Profitability, Solvency, Company Size, and Audit Tenure on Going Concern Audit Opinions (A Study on Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2019-2022) - Candra, Handy; Sigit Mareta (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this research is to determine the extent of the influence of company profitability, the company's methods of solvency in fulfilling its obligations, company size, and the relationship between clients and auditors on going concern audit opinions in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 – 2022. This study uses a descriptive quantitative method with purposive sampling and employs IBM Statistic SPSS Ver 27 for logistic regression measurement. The results of this research indicate that solvency and company size affect going concern audit opinions, whereas profitability and audit tenure do not affect going concern audit opinions.